AN ANALYSIS OF TEACHER’S QUESTIONING IN READING CLASS - Susie Kusumayanthi; Mulyati, Santi (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2021)
Students of EFL (English Foreign Language) classroom need some tools that facilitate them to develop their reading skills. One of the tools is question. Question belongs to one of the most crucial tools in guiding and extending student’s learning (Gattis, 2002:41, as quoted in Sujariati, Rahman, & Mahmud, 2016). This study is descriptive qualitative research. It investigates about questioning in a reading class in one Islamic Senior High School in Bandung. Specifically, it finds out the teacher’s question types and the students’ opinions towards the questions that asked by the teacher in the reading class. In conclusion, mastering English reading skill can be something difficult for students who learn English as foreign language because they do not use the language in their daily lives. However, a teacher can apply both display and referential questions to students. By applying those question types, the students are encouraged to focus in learning reading material in the class and become familiar with some reading exercises that usually appear in English exam.